The association of smoking, use of snuff, and preconception alcohol consumption with spontaneous abortion: A population‐based cohort study - Yvonne Skogsdal; Jan Karlsson; Tanja Tydén; Snehal Patil; Helena Backman (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction It is unclear whether tobacco in early pregnancy and alcohol use preceding pregnancy are associated with spontaneous abortion. The purpose was to investigate if use of tobacco and/or alcohol is associated with spontaneous abortion among women attending antenatal care, and if age and body mass index (BMI) attenuate the risk. Material and Methods A population‐based cohort study based on data from the Swedish Pregnancy Register. All pregnant women having had the first antenatal visit from January 2014 to July 2018 were included (n = 525 604). The register had information about smoking and use of snuff before and in early pregnancy, as well as data on alcohol habits before pregnancy, measured by the Alcohol Use Disorders Identification Test (AUDIT), a validated questionnaire. Logistic regression analysis was used to estimate the association between lifestyle factors and spontaneous abortion, and multiple imputation was used to impute missing data. Results In total, 34 867 (6.6%) pregnancies ended in a spontaneous abortion after the first visit to maternal health care. At the first maternal healthcare visit, daily smoking was reported by 24 214 (5.1%), and 6403 (1.2%) used snuff. For 19 837 (4.2%) women, a high alcohol score was reported for the year preceding pregnancy. After adjusting for potential confounders and multiple imputation, use of tobacco was associated with spontaneous abortion; smoking 1–9 cigarettes/day (adjusted odds ratio [aOR] 1.11, 95% confidence interval [CI] 1.04–1.18), smoking 10 or more cigarettes/day (aOR 1.12, 95% CI 1.–1.26), and use of snuff (aOR 1.20, 95% CI 1.06–1.37). Higher AUDIT scores were not significantly associated with spontaneous abortion (AUDIT 6–9: aOR 1.03, 95% CI 0.97–1.10 and AUDIT 10 or more: aOR 1.07, 95% CI 0.94–1.22). Increasing maternal age showed the highest risk of spontaneous abortion from the age of 35, and BMI of 30 kg/m2 or more increased the risk. There were interactions between different lifestyle factors associated with spontaneous abortion that could either increase or decrease the risk of spontaneous abortion. Conclusions Smoking and use of snuff were associated with an increased risk of spontaneous abortion. The AUDIT scores preceding pregnancy were not associated with an increased risk of spontaneous abortion, which contradicts the results from previous studies.